Finite element simulation of punch through test using a continuous surface cap model - Patil, Aniket; Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2015)
An attempt has been made to calibrate the material model parameters of the continuous surface cap model with data from punch through tests performed in the Northern Gulf of Bothnia. An axisymmetric finite element model has been used to simulate the field tests. The continuous surface cap model based on a combination of elastic-plastic and continuum damage mechanics formulation is used as constitutive model for ice rubble. Material properties such as internal friction angle, cohesion and Young’s modulus are evaluated in a parametric study and the response is compared to the experimental data for the chosen test. An optimization algorithm is used for determining the parameters used for describing the continuous surface cap model. The material model parameters are chosen to get best fit to test load displacement curve. Conclusion has been drawn based on the application of continuous surface cap model on ice rubble. Godkänd; 2015; 20150926 (anipat)